Who are the world's poor? A new profile of global multidimensional poverty. (February 2020) - Robles Aguilar, Gisela; Sumner, Andy
Highlights: We make new estimates of the global multidimensional poverty profile in 2015. The world's multidimensionally poor are predominantly children and young people. The world's multidimensionally poor tend to live in rural areas though they are not necessarily working in agriculture. The extent of the multidimensionality of poverty differs substantially by region. Abstract: This paper is concerned with the following question: Who are the world's multidimensionally poor? To answer this, we compare and contrast the original Alkire–Foster measure of multidimensional poverty with other multidimensional indices in order to show how they differ and the consequences for poverty headcount estimates. We assess the extent of the multidimensionality of poverty using the original Alkire–Foster measure of multidimensional poverty. We then make estimates of the global profile of multidimensional poverty in 2015 using the Alkire–Foster measure and two alternative indices. We conclude that the world's multidimensionally poor are largely young people, residing in rural areas though not necessarily working in agriculture. Overall, the contribution of the paper is to explain how multidimensional poverty indices differ; and to present a new set of estimates of the global multidimensional poverty profile for 2015.